SERVANT LEADERSHIP IN NON-PROFIT ORGANIZATION - Nur Asni Gani; Rony Edward Utama; Jaharuddin Jaharuddin; Andry Priharta; Medo Maulianza (Inovasi, 2022)
The organization is a place for several people or groups of people who carry out activities in achieving goals. In achieving its goals, the organization consists of organizations that have profit and non-profit goals. The development of both profit and non-profit organizations requires a leader with leadership skills. This study analyzes Servant Leadership in non-profit organizations. The method used is qualitative with a case study in a non-profit organization in the South Tangerang area. The study involved four informants with focus group discussions. Each informant gave a statement on the questions posed. The results of this focus group discussion obtained 5 categories of servant leadership in non-profit organizations. The five categories of servant leadership are (1) delegation, (2) integrity, (3) motivation, (4) human resource development, and (5) open communication.Keywords: Servant Leadership, Leadership, Non-Profit Organization